LFC of an interconnected power system with multi-source power generation in deregulated power environment - Parmar, K.P. Singh; Majhi, S.; Kothari, D.P. (International journal of electrical power & energy systems, 2014)
•Interconnected power system with multi-source power generation.•LFC in deregulated environment for all possible contracts.•Optimal output feedback controller is proposed (simple, lesser cost, robust).•More feasible combination of hydro, thermal and gas in each control area.•Simulation results matching with desired values. In this paper, an interconnected power system with multi-source power generation is proposed for load frequency control (LFC) in deregulated power environment. Keeping in view the new power environment, modified LFC scheme is proposed in deregulated environment for multi-source combination of hydro, reheat thermal and gas generating units in each control area. Optimal output feedback controller with pragmatic viewpoint is presented which uses less number of state variables for feedback as measurement of all of the state variables of a large system is impossible in the real world. The proposed controller incorporates all possible power transactions taking place in a deregulated power market. An extensive analysis is done for LFC and it is found that dynamic responses obtained satisfy the LFC requirements in deregulated power environment.